2019
DOI: 10.1111/petr.13472
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of diagnosis and parental attitudes among parents of adolescent kidney recipients

Abstract: The diagnosis of a chronic illness is described as an upsetting event that implies an emotional crisis for parents. Some are able to come to terms with their child's chronic condition and feel a sense of resolution, but for others, strong negative emotions persist through time. The present study examines diagnostic resolution among parents of teenagers with a transplant. The design was qualitative and involved individual interviews with nine parents. Five were donor to their child. Data were analyzed according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…The bidirectional impact of medication adherence on family dynamics cannot be understated. Leblond et al recently reported results from qualitative interviews with the parents of 9 adolescent transplant recipients 10 . Parents identified fears and preoccupations centered around medication adherence as predominant in their relationship with their transplant recipient children.…”
Section: Family‐level Factors That Contribute To and Impact Non‐adhermentioning
confidence: 99%
See 3 more Smart Citations
“…The bidirectional impact of medication adherence on family dynamics cannot be understated. Leblond et al recently reported results from qualitative interviews with the parents of 9 adolescent transplant recipients 10 . Parents identified fears and preoccupations centered around medication adherence as predominant in their relationship with their transplant recipient children.…”
Section: Family‐level Factors That Contribute To and Impact Non‐adhermentioning
confidence: 99%
“…1 There are also tremendous ripple effects with non-adherence impacting the individual's family dynamic, and increasing emotional stress and burden over adherence management ( Figure 1). 10,11 On a greater scale, non-adherence has profound costs in terms of healthcare utilization. It has been estimated that among adult transplant recipients in the United States, medical care costs are over $33,000 greater per individual patient for persistently high versus persistently low adherence groups.…”
Section: Implications Of Non-adherencementioning
confidence: 99%
See 2 more Smart Citations
“…According to a recent study of parents of ESRD children patients, the parent donating a kidney might reduce the parent's sense of guilt. As Leblond et al (2019) put it: “Being the donor might have allowed these parents to overcome their guilt about having contributed to their child's disease by giving life for a second time” (2019, p.5). Accordingly, parents may feel obliged to donate a kidney either because of external pressure from the medical team or from other family members or because of their own internally felt pressure (Leblond et al, 2019).…”
Section: Introductionmentioning
confidence: 99%